Follicular Dendritic Cell Sarcoma - A Case Report - Bhalerao, Sagar Ramesh; Adhav, Aditya Shirish; Nagarkar, Rajnish Vasant (Academia Anatomica International, 2019)
Follicular dendritic cell sarcoma is an uncommon tumor that originates from follicular dendritic cells. The identification and diagnosis of FDCS is not as easy as it has close histological resemblance with non-Hodgkin lymphoma, sarcoma, melanoma, undifferentiated carcinomas, melanoma, and other dendritic or histiocytic cell disease. The definite diagnosis of FDCS can be established with the help of immunohistochemical investigation coupled with imaging modalities such as positron-emission tomography and computed tomography. We present a case of an elderly woman with a history of follicular dendritic tumor. The patient was primarily treated with CHOP chemotherapy in a different hospital. Upon initial investigation in our institution, disease progression was observed. The patient was treated with GEMTAX chemotherapy. The patient showed a partial response to therapy after three cycles of GEMTAX. However, disease progression was observed after six cycles of GEMTAX. The patient was switched to ESHAP, wherein after three cycles partial response to therapy was observed as per PET-CT scans. Despite the use of all three chemotherapy regimens, recurrence was observed. Systemic chemotherapy should be reserved for patients who failed in primary treatment or those with metastatic disease. However, multisite clinical trials should be developed to rationalize optimal treatment strategies for this uncommon disease.